2014
DOI: 10.2753/mtp1069-6679220301
|View full text |Cite
|
Sign up to set email alerts
|

Differential Mediating Effects of Radical and Incremental Innovation on Market Orientation-Performance Relationship: A Meta-Analysis

Abstract: Research shows that innovation mediates the relationship between market orientation and firm performance. However, researchers disagree on whether market orientation leads to differential emphases on radical or incremental innovation, and how each type of innovation influences performance. Drawing on organizational learning theory, this study clarifies these relationships through structural analysis of meta-analytic correlations from 441 samples. The findings indicate that market orientation has similar effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 70 publications
2
70
0
9
Order By: Relevance
“…Consistent with these arguments, a number of studies (Baker and Sinkula, ; Govindarajan et al., ; Lukas and Ferrell, ; Salojärvi and Sainio, ; Zhou et al., ), as well as results from a meta‐analysis (Chang et al., ) provide empirical support for the argument that customer orientation helps radical product innovation. Based on the preceding, the following hypothesis is proposed:…”
Section: Development Of Hypothesesmentioning
confidence: 81%
See 2 more Smart Citations
“…Consistent with these arguments, a number of studies (Baker and Sinkula, ; Govindarajan et al., ; Lukas and Ferrell, ; Salojärvi and Sainio, ; Zhou et al., ), as well as results from a meta‐analysis (Chang et al., ) provide empirical support for the argument that customer orientation helps radical product innovation. Based on the preceding, the following hypothesis is proposed:…”
Section: Development Of Hypothesesmentioning
confidence: 81%
“…Based on a meta‐analysis of the firm innovativeness–firm performance relationship, Rubera and Kirca () report that firms that develop radical product innovations—that is, innovations that utilize novel technologies to create superior customer value (Chandy and Tellis, )—attain a more favorable market position, experience better financial outcomes, and enjoy greater market valuations, relative to their less innovative counterparts. Similarly, from their meta‐analysis of this relationship among goods manufacturers, Chang, Franke, Butler, Musgrove, and Ellinger () conclude that relative to incremental product innovation, radical product innovation has a more positive effect on new product performance and on firm performance. Given the strategic significance of radical product innovation, it is not surprising that issues around how organizations can develop radical product innovations on a sustained basis have received extensive theoretical attention and empirical scrutiny in prior literature (Chandy and Tellis, ; Herrmann, Gassmann, and Eisert, ; Slater, Mohr, and Sengupta, ; Troilo, De Luca, and Atuahene‐Gima, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Slater and Narver (1994) propose that capability to innovate is one of the core capabilities that convert MO into firm performance in enabling the firm to consistently deliver value to its customers. In addition, a number of empirical studies (e.g., Atuahene-Gima, 2005;Chang, Franke, Butler, Musgrove, & Ellinger, 2014;Matear, Osborne, Garrett, & Gray, 2002) suggest MO is an important resource in developing innovative products and improving companies' implementation of product design and launch. Taken together, these studies suggest that a strong MO may, in fact, reinforce the performance implications of effectiveness in new product development and operations.…”
Section: Market Orientation and Business Process Capabilitiesmentioning
confidence: 99%
“…Tellis, Prabhu, and Chandy (2009) reported that the commercialization of radical innovations translates into a firm's financial performance in that it is a stronger predictor of financial performance than other popular measures, such as patents. Chang, Butler, Musgrove, Franke, and Ellinger (2011) reported that radical innovation has a greater mediating impact than incremental innovation on the market orientationfirm performance relationship. Previous research on innovation speed relative to new product performance acknowledged that speedy innovation has a positive impact on marketing performance.…”
Section: Radicalness and Speed Of New Product Development And Marketimentioning
confidence: 99%